Critical Analysis of Islamic Educational Philosophy on the Concept of Essentialist Education - Yuliyanti; Dede Ridho Firdaus; Anis Fuad (Journal of Islamic Education and Intellectual Discourse (JIED), 2025)
This study aims to critically analyze the concept of essentialist education from the perspective of Islamic educational philosophy, particularly in relation to educational goals, curriculum, the role of educators, and student orientation. Using a descriptive qualitative approach with a library research method, this study examines various literature such as books, journals, and scholarly works related to educational philosophy and the essentialist school of thought. The findings show that essentialism emphasizes the mastery of fundamental disciplines, long-standing cultural values, and the authoritative role of teachers in the learning process. Islamic perspectives share common ground with essentialism in terms of discipline formation, knowledge transmission, and character development, yet differ in the need to provide a more balanced space for student participation and potential development. This study concludes that essentialism can contribute to the development of Islamic education when adapted contextually, while maintaining a balance between teacher authority, modern curricular needs, and the spiritual as well as intellectual growth of learners.